Revolutionizing procurement: Unveiling next-gen supplier strategies in UAE's oil & gas sector - Alhammadi, Ali; Yusaf, Talal; Soar, Jeffrey; Mahmood Ali, Bashar; K., Kadirgama; Yousif, Belal F (Elsevier Ltd, 2024)
Procurement is a linchpin in organizational success, securing vital resources that enable top-tier service and product delivery. In fiercely competitive arenas like the oil and gas industry, cultivating robust supplier relationships isn't just beneficial—it's indispensable. Despite the ever-evolving market and myriad factors influencing these interactions, optimizing buyer-supplier dynamics remains paramount. The study delves deep into strategies to fortify procurement partnerships, spotlighting key elements shaping these relationships in the UAE's oil and gas landscape. Utilizing the renowned Kraljic's portfolio model (KPM), the study analyses purchasing strategies and their determinants. Data from a comprehensive online survey with 312 industry stakeholders and stringent reliability tests via SPSS offer compelling insights. Dominant themes include the prevalence of supplier and buyer dominance in ADNOC's procurement of both trivial and significant assets. Notably, no one-size-fits-all strategy emerges for major equipment acquisition, yet supplier dominance proves supremely effective for consumables and minor item procurements. A critical discovery underscores the significant role of employee tenure in shaping purchase decisions and supplier liaisons.